PENGARUH ORGANIZATIONAL CITYZENSHIP BEHAVIOR (OCB), EMPOWERMENT, TOTAL QUALITY MANAGEMENT (TQM), DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN (Studi Kasus pada LUWES GADING SOLO) - Prabandari, Dessi Primawestri Indah; Adi, Suyatmin Waskito (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This study aims to analyze the effect of Organizational Cityzenship BehavOCB), Empowerment, Total Quality Management (TQM) and Self Efficacy on employee performance in Luwes Gading Solo. Data collection techniques through questionnaires. The number of respondents is 100 employees. The research method used is descriptive quantitative. The sampling technique is purposive sampling. The results showed that Empowerment and Self Efficacy had an effect on the performance of Luwes Gading Solo employees, while OCB and TQM had no effect on the performance of Luwes Gading Solo employees.